Description of a new species of deepwater catshark, Bythaelurus giddingsi sp. nov., from the Galápagos Islands (Chondrichthyes: Carcharhiniformes: Scyliorhinidae) - Mccosker, John E.; Long, Douglas J.; Baldwin, Carole C. (Zootaxa, 2012)
We describe Bythaelurus giddingsi sp. nov. based on 7 specimens collected using the submersible Johnson Sea-Link fromdeepwater (428–562 m depth) areas of the Galápagos Islands. It is presumed to be endemic to the archipelago. The newspecies differs from its congeners in its coloration, the length of its anal-fin base, and in other morphological characters. The disjunct distribution of species of the widely-distributed Indo-Pacific genus Bythaelurus is discussed.